DESAIN PEMBELAJARAN HIGH RISK DAN LOW RISK DI SEKOLAH INDONESIA KUALA LUMPUR (SIKL) MALAYSIA ERA NEW NORMAL - Hilyatun Nida; Elya Umi Hanik; Moza Khoirinnida; Nurul Nikmah Rahma Lutfiatin; Tri Widyaningrum (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2021)
This study aims to describe the High Risk and Low Risk learning design in SIKL (Kuala Lumpur Indonesian School) Malaysia in the New Normal Era. This study uses a qualitative approach that is explanatory, which is an explanation of the topic of High Risk and Low Risk learning design. The data analysis techniques used qualitative data analysis techniques, while the data collection techniques use indirect observation, interview, and literature studies. The result and discussion of research, namely learning design is a practice of preparing designs, models, tools (learning media) that can facilitate the learning process. Kuala Lumpur Indonesian School (SIKL) in designing learning during the COVID-19 pandemic divides it into 2 categories, namely High Risk (for students who live far away from school and have to carry out online learning at home) and Low Risk (for students who live with schools and carry out learning at school). In the learning process at the Kuala Lumpur Indonesian School (SIKL) there are 3 stages, namely the planning stage, the implementation stage, and the evaluation stage.